2016
DOI: 10.1038/srep26350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host genes leading to West Nile virus encephalitis in mice brain using RNA-seq analysis

Abstract: Differential host responses may be critical determinants of distinct pathologies of West Nile virus (WNV) NY99 (pathogenic) and WNV Eg101 (non-pathogenic) strains. We employed RNA-seq technology to analyze global differential gene expression in WNV-infected mice brain and to identify the host cellular factors leading to lethal encephalitis. We identified 1,400 and 278 transcripts, which were differentially expressed after WNV NY99 and WNV Eg101 infections, respectively, and 147 genes were common to infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 67 publications
5
40
0
Order By: Relevance
“…In human cell lines, expression of TIM1 promotes infection of WNV virus-like particles (VLPs) [33,34], suggesting that the upregulation of TIM1 seen in zebra finches may promote viral entry as well. Similarly, C-C motif chemokine (ENSTGUG00000005295) is upregulated in our study at 2 dpi and in previous human cell line and mouse experiments, suggesting a conserved role in chemokine production following WNV infection [31,35,36]. Apolipoprotein D (APOD), a gene typically involved in brain injury and potentially responding to the neurodegenerative nature of WNV, is upregulated in WNV-infected mice [37], as well as in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In human cell lines, expression of TIM1 promotes infection of WNV virus-like particles (VLPs) [33,34], suggesting that the upregulation of TIM1 seen in zebra finches may promote viral entry as well. Similarly, C-C motif chemokine (ENSTGUG00000005295) is upregulated in our study at 2 dpi and in previous human cell line and mouse experiments, suggesting a conserved role in chemokine production following WNV infection [31,35,36]. Apolipoprotein D (APOD), a gene typically involved in brain injury and potentially responding to the neurodegenerative nature of WNV, is upregulated in WNV-infected mice [37], as well as in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, a recent study that evaluated the brain expression of chemokines in peripherally lyssavirus‐infected mice revealed that CCL2, CCL5 and CXCL10 immunolabelling pattern displayed a similar distribution to viral antigen and inflammatory lesions (Hicks et al, ). Molecular chemokine expression (including CCL2, CCL5 and CXCL10) has been observed to be a key differentiating factor in pathogenic WNV strains in comparison to non‐pathogenic strains (Kumar, Belcaid, & Nerurkar, ), suggesting an important role for chemokines in the development of encephalitis in viral infections of the CNS (Savarin & Bergmann, ). In addition to chemokines, the elevation and increased expression of other chemotactic factors, as migratory inhibitor factor (MIF), have been related with the development of acute WNV infection and CNS inflammation in humans and MIF knockout BALB/c mice inoculated intraperitoneally (Arjona et al, ). In the present study, the increase of perivascular cuffs and WNV positive neurons were also associated with an increase of chemokine immunolabelling.…”
Section: Discussionmentioning
confidence: 99%
“…Virus RNA levels were analyzed in the supernatant and cell lysates by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). RNA from cell culture supernatants was extracted using a Viral RNA Mini Kit (Qiagen) and RNA from cell lysates was extracted using a RNeasy Mini Kit (Qiagen) as described previously (20,21,23). qRT-PCR was used to measure viral RNA levels using previously published primers and probes specific for the SARS-COV-2.…”
Section: Viral Rna Quantificationmentioning
confidence: 99%
“…For mRNA analysis of IL-6, IL-1β, TNFα and NF-kB, cDNA was prepared from RNA isolated from the cell lysates using a iScript™ cDNA Synthesis Kit (Bio-Rad, Hercules, CA, USA), and qRT-PCR was conducted as described previously (21,23,24). The primer sequences used for qRT-PCR are listed in Table 1.…”
Section: Cytokine Analysismentioning
confidence: 99%